A Global Society of Reciprocity (Asian Journal of Social Science Studies, 2022)
This essay concerns the claim that egalitarian principles of distributive justice apply within states but not between them. The analysis will rely primarily on the arguments made in Andrea Sangiovanni‟s article. Due to the limit of words and attention, I shall only discuss issues of inequality of resources/wealth and focus only on Sangiovanni‟s arguments on relational claims. I will first demonstrate his arguments, in relational account, how Globalist Egalitarian does not justify an obligation of distributive justice and how Internationalism, in accordance to his idea of Reciprocity, does. Later I will demonstrate, with his logic, why global distributive justice is justified and desirable. Thus, proves the claim above wrong.